1978
DOI: 10.1007/bf00272686
|View full text |Cite
|
Sign up to set email alerts
|

Leaf mutants in diploid red clover (Trifolium pratense L.)

Abstract: Leaf mutants were isolated and genetically stabilised in diploid red clover (Trifolium pratense). The major alteration showed normal trifoliolate leaves changed into multifoliolate leaves composed of 4-, 5-, 6- and 7 leaflets. As a result of recombination with other mutant alleles several genotypes were isolated with a different mode of leaf setting, different shapes and sizes of leaflets, variations in the whole plant habit, etc. A careful description was made of the mutant morphology and the development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A gene for glabrousness was only known in indica, but not in japonica varieties. The seed production of these genotypes is not negatively influenced (Jaranowski and Broda 1978). Some of them show good yielding properties (Hiraiwa and Tanaka 1979).…”
Section: Leaf Mutants Of Agronomic Interestmentioning
confidence: 99%
“…A gene for glabrousness was only known in indica, but not in japonica varieties. The seed production of these genotypes is not negatively influenced (Jaranowski and Broda 1978). Some of them show good yielding properties (Hiraiwa and Tanaka 1979).…”
Section: Leaf Mutants Of Agronomic Interestmentioning
confidence: 99%
“…Because the basal species of Trifolium often have pentafoliolate leaves (Ellison et al, 2006; Zohary and Heller, 1984), it is believed that the genus Trifolium originated from multifoliolate ancestors and that the number of leaflets was reduced during evolutionary time (Eames, 1961; Jaranowski and Broda, 1978; Zohary and Heller, 1984). The presence of a dominant locus that inhibits the expression of multifoliolate leaves, leading to trifoliolate leaves in white clover, supports the premise that leaflet number suppressors in the Fabaceae in general, and Trifolium in particular, resulted in lower leaflet number (Eames, 1961; Zohary and Heller, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In red clover (T. pratense L.), the multifoliolate trait was fi rst studied by Simon (1962), who determined it was conditioned by homozygous recessive alleles at one of two loci. Also studying red clover, Jaranowski and Broda (1978) determined that the multifoliolate trait was controlled by homozygous recessive alleles at three loci, and Taylor (1982) determined it was a quantitative recessive trait.…”
Section: Researchmentioning
confidence: 99%
“…Knight (1969) studied the inheritance of multifoliolate leaves, glabrous leaves, and petiolulate leaflet attachment in crimson clover, T. incarnatum L. and reported that each of the trait to be controlled by a single recessive gene pair as intermediate forms were not observed in segregating population. Jaranowski and Broda (1978) while studying leaf mutants in diploid red clover (T. pratense) reported that the leaf alteration (complexity) is governed by at least three recessive pairs of alleles of additive action. The phenotypic expression of the altered leaves depends simply on the number of recessive alleles.…”
Section: Expression Of Multifoliate Traitmentioning
confidence: 99%
“…One such reference to multifoliolate leaves in white clover (Trifolium repens L.) is in the registration of FL-ML white clover germplasm (Baltensperger et al 1991). Knight (1969) in Trifolium incarnatum and Jaranowski and Broda (1978) in Trifolium pratense also reported multifoliate leaf formation. However, there is no report of developing pure pentafoliate in any Trifloium species.…”
mentioning
confidence: 99%